Carta de Antonio R. Barceló a Roberto H. Todd - Barceló, Antonio R.; Todd, Roberto H. (My University, 1931)
Recomendación para Cecilia Osorio.
Keywords: Osorio, Cecilia; Barceló, Antonio R., 1868-1938